The association between the parent-child relationship and parental personality development during the child's transition to adolescence: A longitudinal study - Hutteman, Roos (Array, 2011)
Changes in the parent-child relationship during the transition to adolescence and the influence of this relationship on the child’s development have been widely studied. This transition is a period of many changes, not only for the adolescent but also for his or her social environment. However, the effect of the parent-adolescent relationship on the development of parents’ personality during this period of life has been surprisingly understudied. In the present contribution, we investigated the influence of the quality of the parent-child relationship during the child’s transition to adolescence on changes in the Big Five personality factors of parents. To do so, we assessed a group of 719 Croatian adolescents in grades 4-8 and their parents from the Zagreb Personality and Parenting Longitudinal Study (ZAPPLOS). They were assessed 3 times, with a 1-year interval between the assessments. We found the quality of the parent-adolescent relationship to be associated to changes in several parental personality traits. For example, we found conflict between parent and child to be related to a decrease in both emotional stability and agreeableness of the parent, whereas parenting self-efficacy was associated with an increase in these traits. We will discuss differences between the development of fathers and mothers and we will investigate the parent-child relationship from both the parents’ and the children’s perspective. Studying parental personality development in relation to the parent-child relationship will shed light on the processes underlying personality development in midlife.